KARAKTER (ADAB) GURU DAN MURID PERSPEKTIF IBN JAMÂ’AH AL-SYÂFI’Î - Rahendra Maya (Sekolah Tinggi Agama Islam Al Hidayah, 2017)
The main purpose of education, both general education and Islamic education, is to moled noble character (or akhlak or adab) of student. Due to this urgent position of that character, especially teacher’s and student’s character, so this study is aimed at discussing the concept of character education according to a great Islamic scholar.This studi research is focused on the background of the deterioration of education, both general education and Islamic education, mainly due to the rampant characterdecadence, both from teachers and from students. On the other hand, a character education program which has been programmed in Indonesia, although it is actually a good program, but is considered still keep a number of problematic concepts, criticism and claims of failure and suggestions for improvements. For the Muslims, these programs must be harmonized with even very specific distinctive character, namely the Islamic character based on the rules of Islam in general and Islamic characters (Islamiyyah etiquettes) specifically.Therefore, this research is formulated to describe teacher’s and student’s character (adab al-’âlim wa al-muta’allim)based on Ibn Jamâ’ah thought and find ways to apply it strategically-conceptual in character education programs in Indonesia through the improvement of teacher’s dan student’s character based on figures perspective. This research is a qualitative research to approach the study of literature (library research)which is descriptive-explanative to be analyzed by the method of content analysis in his masterpiecepedagogical-educative of the book ‘Tadzkirah al-Sâmi’ wa al-Mutakallim fî Âdâb al-’Âlim wa al-Muta’allim’ as its primary text through documentation method.